2020
DOI: 10.3390/ma13081958
|View full text |Cite
|
Sign up to set email alerts
|

Improving Radiation Resistance of GaInP/GaInAs/Ge Triple-Junction Solar Cells Using GaInP Back-Surface Field in the Middle Subcell

Abstract: This paper studies the radiation resistance for GaInP/GaInAs/Ge triple-junction space solar cells with a GaInP back-surface field (BSF) in the GaInAs middle subcell compared with those with an AlGaAs BSF. The results show that the initial electrical performance is almost the same for both of them. However, the radiation resistance of the GaInP BSF cell was improved. After irradiation by 1 MeV electron beam with a cumulative dose of 1015 e/cm2, the Jsc declined by 4.73% and 6.61% for the GaInP BSF cell and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…They found that the incidence of electrons introduces lattice defects in the cells that act as recombination centers, directly impacting carrier lifetimes. A reviewed report found that radiation damage in solar cells causes a reduction in minority carrier diffusion length and thereby reduces overall conversion efficiency [ 39 , 40 , 41 , 42 , 43 ]. Based on the above reviews, irradiation by high-energy radiation particles degrade the physical properties of irradiated semiconductor materials.…”
Section: Introductionmentioning
confidence: 99%
“…They found that the incidence of electrons introduces lattice defects in the cells that act as recombination centers, directly impacting carrier lifetimes. A reviewed report found that radiation damage in solar cells causes a reduction in minority carrier diffusion length and thereby reduces overall conversion efficiency [ 39 , 40 , 41 , 42 , 43 ]. Based on the above reviews, irradiation by high-energy radiation particles degrade the physical properties of irradiated semiconductor materials.…”
Section: Introductionmentioning
confidence: 99%
“…The degradation of electrical performance in solar cells directly affects the life-time of space missions. The researchers aimed at improving the radiation resistance of solar cells by adding a certain thickness of protective cover to the solar cell to shield the damage of certain particles [23], using back-surface (BSF) [24] or distributed Bragg reflector (DBR) [25], and thinning the base layer thickness of the current-limiting subcell [26], or using the p-i-n structure and different doping methods for multi-junction solar cells [27]. The experimental observations show that annealing of the multi-junction solar cell can restore certain electrical properties after being radiated by high-energy particles [28].…”
Section: Introductionmentioning
confidence: 99%
“…The radiation hardness is improved by changing the middle-layer BSF from AlGaAs to Ga 0.502 In 0.498 P. [129] The electrons radiation degrades mostly the GaAs-based middle layer. [129] The use of BRs allows to use external PV cells (light splitting) while the main cell is thinned, increasing the efficiency and radiation hardness, respectively. [145] GaInP/Ga 0.99 In 0.01 As/Ge The efficiency is increased by using double BR while optimizing the layers thickness.…”
Section: (Lm) Gainp/gainas/gementioning
confidence: 99%